An Analysis of the Contemporary Use of Film as A Medium for Investigating Social Issues - Mohamed.S.H, Sheik; Nirmala, M.; Elango, S (La Ogi : English Language Journal, 2024)
The study reveals that movies that address social issues can increase awareness and spark discussion among viewers. This can lead to increased empathy towards marginalised communities and a greater understanding of complex societal problems. Furthermore, these films have the potential to inspire individuals to take action and advocate for change in their communities. In this way, cinema serves as a powerful tool for social change and activism. Films can influence audiences and bring about social change, expediting justice and encouraging action against issues like farmers' and environmental problems. The success of films like Ketika Mas Gagah Pergi, Tanda Tanya, Uriyadi, Thanga Magal, Tolet, Thaneer Thannee, Kaththi, Karuthamma, Pariyerum Perumal, and Merkku Thotarchi Malai can significantly impact society. These movies shed light on various social issues such as water scarcity, farmer suicides, caste discrimination, and environmental degradation. Thaneer Thanneer is a Tamil movie that exposes the hardships of poor villages and corrupt politicians, inspiring people to fight for their rights. By portraying these issues on the big screen, filmmakers are able to reach a wide audience and create a platform for dialogue and action. Through the power of storytelling, these films have the potential to not only entertain but also educate and inspire viewers to take a stand and work towards positive change in society. Socially conscious films such as Thaneer Thannee and others have the power to spark social movements and bring about real-world change, which cannot be underestimated